2020
DOI: 10.1111/ele.13584
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and coordinated evolution of plant hydraulic traits

Abstract: Hydraulic properties control plant responses to climate and are likely to be under strong selective pressure, but their macro-evolutionary history remains poorly characterised. To fill this gap, we compiled a global dataset of hydraulic traits describing xylem conductivity (K s), xylem resistance to embolism (P50), sapwood allocation relative to leaf area (Hv) and drought exposure (w min), and matched it with global seed plant phylogenies. Individually, these traits present medium to high levels of phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 73 publications
4
80
2
1
Order By: Relevance
“…high water transport efficiency) are also more vulnerable to embolism (low |Ψ P50 | and low safety) and vice versa (Venturas et al, 2017). However, this tradeoff appears to be weak at the global scale across species, at least as captured with current measurement techniques (Gleason et al, 2016; Sanchez‐Martinez et al, 2020). At the leaf level, another key component is the water potential at turgor‐loss point (Ψ TLP ), which is closely associated with drought tolerance and habitat water availability (Bartlett et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…high water transport efficiency) are also more vulnerable to embolism (low |Ψ P50 | and low safety) and vice versa (Venturas et al, 2017). However, this tradeoff appears to be weak at the global scale across species, at least as captured with current measurement techniques (Gleason et al, 2016; Sanchez‐Martinez et al, 2020). At the leaf level, another key component is the water potential at turgor‐loss point (Ψ TLP ), which is closely associated with drought tolerance and habitat water availability (Bartlett et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We analysed phylogenetic correlation between K leaf and P50 leaf in this study, and the result indicated that there was an evolutionary integration between leaf hydraulic efficiency and safety (electronic supplementary material, figure S2). A recent global phylogenetic analysis of stem hydraulic traits did not find a significant evolutionary trade-off between hydraulic conductivity and cavitation resistance at the genus level of phylogeny, because the two stem hydraulic traits depend on several anatomical properties that might not necessarily co-evolve [43]. Therefore, the evolutionary correlation between hydraulic efficiency and safety needs to be further clarified.…”
Section: Discussionmentioning
confidence: 98%
“…S6). Hence, Model 2 provides a novel view on the weak relationship between specific hydraulic conductivity and P 50 values for many angiosperm species (Hacke et al ., 2006; Loepfe et al ., 2007; Gleason et al ., 2016; Sanchez‐Martinez et al ., 2020). It would also be interesting to examine whether considerable variation in T PM and N PIT leads to considerable variation in the hydraulic resistance of pit membranes.…”
Section: Discussionmentioning
confidence: 99%